Evaluation of carbide capacity in CaO-based ternary systems for refining process (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Refining slags are widely used in the production of high-value-added alloys and special steels. The removal of impurities depends on the mass transfer between the slag-metal interface, and the carbide capacity of the refining slags is crucial to control of the carbon content in the final products. A phenomenological model is introduced in this article for the calculation of carbide capacity of different CaO-based ternary refining slags. The contour lines of carbide capacity in CaO-Al2O3-CaF2, CaO-SiO2-CaF2 CaO-SiO2-MnO systems are calculated based on limited experimental data by the present model. The experimental data within the calculation boundary are compared with the predicted values and satisfactory agreements are observed with the mean deviation being 1.4%, 2.3% and 1.6% respectively for three systems. The present model is powerful and flexible in the calculation of carbide capacity of CaO-based ternary refining slags and can be applied to other systems.